BOOK REVIEW: PERSPECTIVES AND REFLECTIONS ON RACIAL LITERACY AS AN APPROACH TO CRITICAL WRITING INSTRUCTION - Nanquil, Luisito Manalansan (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
This paper examined and reviewed the book authored by two ESL experts. It was discovered by the researcher-reviewer that racial literacy is important in teaching critical writing. Teaching writing skills is not a piece of cake. Learners always come to school with varied interests and motivations but it may not indicate they are inclined to writing. To make learners proficient in writing is indeed a challenging task on the part of the teacher. A racial literacy is one of the effective and appropriate approaches that can be infused by the teacher to make classroom experience holistic and engaging. This article depicts issues about the use of the approach in an EFL and ESL classroom. Furthermore, some steps to racial literacy were examined by the researcher to ensure their effectiveness in teaching composition writing.